The Relevance of Muamalah Hadiths in Addressing the Challenges of Modern Buying and Selling: A Study of Contemporary Islamic Law Responses - Muhammad Faqih Choiruddin; Endad Musaddad (Aslama: Journal of Islamic Studies, 2025)
This study explores the relevance of prophetic traditions (hadiths) on commercial transactions (muamalah) in addressing the complexities of modern economic practices shaped by digital advancements. In an era of globalization and digitalization, trade activities have undergone a major transformation through the rise of e-commerce, Islamic fintech, and digital asset transactions. Employing a normative qualitative approach and library research method, the analysis focuses on selected hadiths related to economic ethics and the responses of contemporary Islamic legal authorities, including DSN-MUI and the International Islamic Fiqh Academy. The findings indicate that although originating in a 7th-century Arab context, these hadiths remain applicable as ethical and legal references in today’s digital economy. Core Islamic values such as honesty, justice, transparency, and social responsibility continue to serve as foundational principles for lawful and fair transactions. Therefore, integrating hadith-based values into contemporary Islamic economic law is essential to achieving a just, ethical, and spiritually grounded financial system in line with maqāṣid al-sharī‘ah.